GAMBARAN PEMERIKSAAN ANTIBODI HIV PADA SOPIR TAKSI DI WILAYAH KELURAHAN KUTA KABUPATEN BADUNG - Anggraeni Suarsana; A.A. Ngurah Subawa; Lia Cahya Sari (Bali Medika Jurnal, 2017)
Introduction: AIDS is a collection of certain clinical conditions that are the outcome of infection by HIV. Currently, the problem of HIV / AIDS is a big problem that threatens many countries around the world, one of them is Indonesia. HIV / AIDS is much affected by the productive age population and more affected by men than women. The taxi driver job has a lot of time on the highway. Taxi drivers will be vulnerable to HIV transmission when performing high-risk behaviors against its HIV transmission. This study aims to find out the description of HIV antibody examination on taxi drivers in Kelurahan Kuta Kabupaten Badung. Method: The type of research used is descriptive research. This research was conducted on May 2017. The sampling of the research was done at UPT. Puskesmas Kuta 1 and the examination was conducted at Health Analyst Laboratory of STIKes Wira Medika Bali. The population used in this study are all taxi drivers who are in Kelurahan Kuta Kabupaten Badung and the samples are 33 drivers. The method used in this research is Rapid Test / Immunochromatography method. The data have been analyzed and presented in tabular form. Result: The results of this study were all samples of taxi drivers showed non-reactive results against HIV antibodies. Discussion: This means no HIV antibodies found in taxi drivers serum.